Meta-analyzing the efficacy of 3D printed models in anatomy education - Ye, Zhen; Jiang, Hanming; Bai, Suyun; Wang, Tao; Yang, Duxiao; Hou, Haifeng; Zhang, Yuanying; Yi, Shuying (Frontiers in Bioengineering and Biotechnology, 2023)
Three-dimensional printing models (3DPs) have been widely used in medical anatomy training. However, the 3DPs evaluation results differ depending on such factors as the training objects, experimental design, organ parts, and test content. Thus, this systematic evaluation was carried out to better understand the role of 3DPs in different populations and different experimental designs. Controlled studies of 3DPs were retrieved from PubMed and Web of Science databases, where the participants were medical students or residents. The teaching content is the anatomical knowledge of human organs. One evaluation indicator is the mastery of anatomical knowledge after training, and the other is the satisfaction of participants with 3DPs. On the whole, the performance of the 3DPs group was higher than that of the control group; however, there was no statistical difference in the resident subgroup, and there was no statistical difference for 3DPs vs 3D visual imaging (3DI). In terms of satisfaction rate, the summary data showed that the difference between the 3DPs group (83.6%) vs the control group (69.6%) (binary variable) was not statistically significant, with p > 0.05. 3DPs has a positive effect on anatomy teaching, although there are no statistical differences in the performance tests of individual subgroups; participants generally had good evaluations and satisfaction with 3DPs. 3DPs still faces challenges in production cost, raw material source, authenticity, durability, etc. The future of 3D-printing-model-assisted anatomy teaching is worthy of expectation.